2022
DOI: 10.3390/nu14061228
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Fruit and Vegetable Intake and Low Potassium Intake Aggravate Early Renal Damage in Children: A Longitudinal Study

Abstract: Insufficient fruit and vegetable intake (FVI) and low potassium intake are associated with many non-communicable diseases, but the association with early renal damage in children is uncertain. We aimed to identify the associations of early renal damage with insufficient FVI and daily potassium intake in a general pediatric population. We conducted four waves of urine assays based on our child cohort (PROC) study from October 2018 to November 2019 in Beijing, China. We investigated FVI and other lifestyle statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Z-scores of height, weight, and body mass index (BMI) were calculated using 2007 WHO standards and standardized SBP was calculated by age and sex group. Lifestyle information were reported by parents using self-administrated questionnaires, including sleep duration (Children's Sleep Habits Questionnaire [CSHQ]) ( 26 , 27 ), fruit and vegetable intake (FVI; 16-item Mediterranean Diet Quality Index in children and adolescents [KIDMED]) ( 23 , 28 ), and computer/cell phone screen time and PA time (self-administrated questionnaire, including 17 activities indoor and outdoor lasting at least 15 min, based on Children's Leisure Activities Study Survey Chinese version [CLASS-C]) ( 29 ). Short sleep for children was defined as sleep duration <10 h/day.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Z-scores of height, weight, and body mass index (BMI) were calculated using 2007 WHO standards and standardized SBP was calculated by age and sex group. Lifestyle information were reported by parents using self-administrated questionnaires, including sleep duration (Children's Sleep Habits Questionnaire [CSHQ]) ( 26 , 27 ), fruit and vegetable intake (FVI; 16-item Mediterranean Diet Quality Index in children and adolescents [KIDMED]) ( 23 , 28 ), and computer/cell phone screen time and PA time (self-administrated questionnaire, including 17 activities indoor and outdoor lasting at least 15 min, based on Children's Leisure Activities Study Survey Chinese version [CLASS-C]) ( 29 ). Short sleep for children was defined as sleep duration <10 h/day.…”
Section: Methodsmentioning
confidence: 99%
“…ChiCTR2100044027, official website as https://www.procstudy.com ) enrolled 1,914 children aged 6–8 years newly in six non-boarding primary schools in Beijing in 2018 [detailed elsewhere ( 22 )]. All participants were recruited from the PROC cohort and were followed for four waves of repeated urine assays from October 2018 to November 2019 [detailed elsewhere ( 23 )]. In brief, the wave 1 of urine assay was conducted at baseline and waves 2–4 of urine assays were conducted within a 1-week span periodically during the 1-year follow-up visit ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reported that moderate fruit consumption was associated with lower odds of lipid disorders [ 2 ] and that high fruit and vegetable intake (FVI) could reduce asthma-related illness [ 3 ]. However, insufficient FVI and low potassium intake aggravate early renal damage in children [ 4 ]. Cereals are a major source of dietary energy and a good source of many micronutrients and dietary fiber.…”
mentioning
confidence: 99%